Public Debt and Budget Deficit Threshold Levels on New Fiscal Sustainability Indicator - Cahyadin, Malik; Sarmidi, Tamat; Khalid, Norlin; Law, Siong Hook (Faculty of Economic and Business, Universitas Islam Negeri Syarif Hidayatullah, 2023)
Fiscal sustainability can be determined and assessed using financial technology (FinTech). Consequently, a new indicator of fiscal sustainability can be constructed. This study also estimates threshold levels of public debt and budget deficit by considering institutions for 88 developing and 35 developed countries in 2014 and 2017. The principal component analysis (PCA) and the cross-section threshold regression are employed. The main findings revealed that the threshold levels of public debt-to-GDP ratio for developed and developing countries in 2014 were 100.37% and 63.04%, while that in 2017 were 90.09% and 84.28%, respectively. Moreover, the threshold levels of budget deficit-to-GDP ratio for developed and developing countries in 2014 were -3.04% and -1.24%, while those in 2017 were -0.97% and -5.75%, respectively. Therefore, policymakers should emphasize a certain public debt and budget deficit level to warrant a fiscally sustainable level.JEL Classification: C13, E62, H60 How to Cite:Cahyadin, M., Sarmidi, T., Khalid, N. & Law, S. H. (2023). Public Debt and Budget Deficit Threshold Levels on New Fiscal Sustainability Indicator. Signifikan: Jurnal Ilmu Ekonomi, 12(1), 97-116. https://doi.org/10.15408/sjie.v12i1.31005.